Effect of Structural Components of Modified Gel Carrier on Enzymatic Properties of Immobilized Industrial Strain of Lactococcus lactis after Low-Temperature Storage - Petrov, Ilya V.; Buriak, Iryna A.; Cherkashina, Yana O. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 164